Synthesis, Characterization, X-Ray Crystal Structures and Antibacterial Activity of Cobalt(III) Complexes Derived from 5-Bromo-2-((2-(phenylamino)ethylimino)methyl)phenol - Cheng Liu (Acta Chimica Slovenica, 2021)
Two new and similar cobalt(III) complexes, [CoL2]·NO3 (1) and [CoL2]·Cl (2), where L is 5-bromo-2-((2-(phenylamino)ethylimino)methyl)phenolate, have been synthesized and characterized by IR and UV-Vis spectra. Structures of the complexes were confirmed by single crystal X-ray determination. The Co atoms in the complexes are in octahedral coordination, with the donor atoms come from the two Schiff base ligands, viz. phenolate oxygen, and imino and amino nitrogen. The anions of the cobalt salts crystallized as counteranions in the complexes. The complexes were assayed for antibacterial activities by MTT method.